Warming and water deficit impact leaf photosynthesis and decrease forage quality and digestibility of a C4 tropical grass. Issue 2 (26th January 2019) - Habermann, Eduardo; Dias de Oliveira, Eduardo Augusto; Contin, Daniele Ribeiro; Delvecchio, Gustavo; Viciedo, Dilier Olivera; de Moraes, Marcela Aparecida; de Mello Prado, Renato; de Pinho Costa, Kátia Aparecida; Braga, Marcia Regina; Martinez, Carlos Alberto
Abstract : Global warming is predicted to cause more intense extreme events such as heat waves, flooding and severe droughts, producing significant effects on agriculture. In tropics, climate change will severely impact livestock production affecting water availability, forage quality and food for cattle. We investigated the isolated and combined effects of soil water deficit ( wS ) and + 2°C increase in canopy temperature ( eT ) on leaf gas exchange, chlorophyll fluorescence, carbohydrate content, forage quality and in vitro dry matter digestibility (IVDMD) of a field‐grown C4 tropical forage grass Panicum maximum Jacq. using a temperature‐free air‐controlled enhancement (T‐FACE) system. The wS and eT treatments showed no effects on photosystem II photochemistry. However, wS under ambient temperature decreased net photosynthesis rate ( A ), stomatal conductance ( g s ) and maximum rate of carboxylation of Rubisco ( V cmax ), leading to a reduced starch content in leaves. A 16% reduction in leaf dry mass (LDM) and reduction in forage quality by increasing fibers, reducing crude protein (CP) and decreasing the IVDMD was also observed by effect of wS . Warming under adequate soil moisture ( eT ) significantly increased LDM by 25% but reduced the forage quality, increasing the lignin content and reducing starch, CP and digestibility. The combined wSeT treatment reduced A, g s, V cmax and the forage quality. When compared to control, the lignin content in leaves increased by 43, 28 and 17% in wS, eT and wSeT, respectively, causing a significant reduction in IVDMD. We concluded that despite physiological mechanisms to acclimate to warming, both warming and water deficit will impair the quality and digestibility of C4 tropical pastures.